The Relationship Between Family Knowledge and Attitudes Toward the Prevention of Dengue Fever in Children - Putri, Dhian Eka; Nurvinanda, Rezka; Lestari, Indri Puji (Inspirasi Foundation, 2025)
Introduction: Dengue Hemorrhagic Fever (DHF) remains a major public health concern in tropical countries, including Indonesia, where recurring outbreaks continue to contribute significantly to morbidity and mortality rates. Despite various preventive programs, such as mosquito nest eradication (PSN) and public education, the increasing incidence of DHF—especially among children—indicates that community knowledge and attitudes toward prevention remain insufficient. Objective: This study aims to determine the relationship between family knowledge and attitudes toward the prevention of DHF in children in the working area of Puskesmas Mentok in 2025. Method: This study used a cross-sectional design with a correlational analytic approach. The sampling technique was purposive sampling, involving 100 respondents who were families with children in the working area of Puskesmas Mentok. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted through univariate and bivariate analysis using the Chi-Square test with a significance level of 0.05 Result: The results of this study showed a significant relationship between family knowledge and DHF prevention in children (p=0.001). There was also a significant relationship between family attitudes and DHF prevention in children (p=0.001). This indicates that family knowledge and attitudes positively influence preventive actions against DHF. Conclusion: The conclusion of this study is that the higher the level of family knowledge and attitudes, the better the preventive actions for DHF in children. It is recommended that Puskesmas and related institutions continuously enhance health promotion and family health education programs through counseling, healthy environment campaigns, and family education to increase public awareness in DHF prevention.